Tratamiento informativo de radio libre en el noticiero matinal: Guerra-Ucrania-Rusia - Jimenez Arevalo, Shirley Rossana (2022)
The present case study seeks to analyze the informative treatment of Radio Libre in its Morning News on the Ukraine-Russia war, through the analysis of 4 transmitted notes, in addition, there are many versions that are poured in times of war by one or the other situation, however, maintaining a fair line and verticality in the dissemination of information is very important and generates significant contributions in the theoretical contributions that derive from it for the different areas included in the academic and social. Likewise, for the collection of information, the analysis of the observation sheets of the news broadcast by the morning newscast of Radio Libre, as well as an interview with the director of the radio, was considered, and in conclusion, it was determined that in general, when referring to the treatment of information on the war between Russia and Ukraine in the morning news, it can be inferred that it maintains reliable international sources, maintains information treatment policies that do not allow ideological bias or their dissemination without prior verification, therefore, it is recommended that, when referring to the treatment of the information on the war between Russia and Ukraine in the morning news, the impartiality evidenced in this case study should be maintained and refer to reliable international sources, maintain policies in the treatment of information that does not allow ideological bias or the dissemination of the same but without prior verification.